(untitled) (Research, Society and Development, 2020)
Organizational Culture is a construct of fundamental importance for managers in organizations. For, in general, it guides the adoption of behaviors by the employee of the institution. This construct can be understood as a model of basic assumptions that certain groups create, discover, or develop during the learning process to deal with problems of external adaptation and internal integration in the work environment. This study aimed to evaluate the psychometric characteristics of the brazilian instrument for assessment of organizational culture in workers of a Public Higher Education Institution. For this purpose, data were collected with 492 servers, 54% were men, 21-69 years (mean = 44.42; dp = 10.87), 54% were married and average service time was 10.74 years. Descriptive analyzes, confirmatory factorial analysis and modeling of structural equations with SPSS and AMOS.21 were performed. The results indicated indexes satisfactory according to the current literature for that measure in the context of the present study.